Efficacy and safety of daclatasvir and asunaprevir for hepatitis C virus genotype 1b infection - Nam, Hee Chul (Clin Mol Hepatol, 2016)
BACKGROUND/AIMS: The treatment strategy for hepatitis C virus (HCV) has been changing rapidly since the introduction of direct-acting antivirals such as daclatasvir (DCV) and asunaprevir (ASV). We evaluated the efficacy and safety of DCV and ASV for HCV in real-life practice. METHODS: Patients were treated with 60 mg of DCV once daily plus 200 mg of ASV twice daily for 24 weeks, and followed for 12 weeks. The primary endpoint was a sustained virological response at 12 weeks after treatment (SVR(12)) and safety. RESULTS: This retrospective study included eight patients with chronic HCV genotype 1b infection. All of the enrolled patients were diagnosed with liver cirrhosis, and their mean age was 65.75 years. One patient was a nonresponder and two patients relapsed with previous pegylated interferon (PegIFN) and ribavirin (RBV) treatment. None of the patient showed NS5A mutation. An SVR(12) was achieved in 88% of cases by the DCV and ASV combination therapy. The serum transaminase level and the aspartate-aminotransferase-to-platelet ratio were improved after the treatment. DCV and ASV were well tolerated in most of the patients, with treatment discontinuation due to adverse events (elevated liver enzyme and decompensation) occurring in two patients. CONCLUSION: In this study, combination of DCV and ASV treatment achieved a high sustained virological response with few adverse events even in those with cirrhosis, advanced age, and nonresponse/relapse to previous interferon-based therapy. Close monitoring of safety issues may be necessary when treating chronic HCV patients receiving DCV and ASV, especially in older patient and those with cirrhosis.